SEED QUALITY, GERMINATION, AND VIGOR OF SOYBEAN (GLYCINE MAX L.) SEEDS AS INFLUENCED BY MOISTURE CONTENT AND CONTAINERS - Cagasan, Ulysses A (Journal of Agriculture and Technology Management, 2022)
Moisture content and types of containers used to store seeds are the most critical factors influencing the rate of deterioration in seeds. This study aimed to evaluate the seed quality, germination, and vigor of soybean seeds using different containers under two moisture contents upon storage. The experiment was arranged in CRD with a 2 x 3 factorial experiment with three replications. Levels of % MC (10% and 13%) served as the main plot, and different containers (plastic bag, paper bag, and bottle) served as the sub-subplots. Four months after storage, comparing the two moisture levels of the seeds, data showed increasing values of moisture contents regardless of the container used in the study. Moreover, using the paper bag as a container showed a significant increase in moisture content (MC) under 13 %. Initial % germination in a composite sample of soybean seeds was high (81% under 10 %MC and 83% in 13% MC) before the seed germination test. Four (4) months after storage, the quality and % germination were significantly decreased to 32% and 60% seed germination under 13 % MC and 10%MC, respectively. Moreover, % seed germination was only 35% and 30% in plastic and paper bag containers. However, it showed a 70% germination when the seeds were stored in closed bottles. Moreover, the seed vigor of soybean seeds was 3.43% only after the seeds were planted in the field and exposed to open field conditions regardless of moisture and containers used for storage.